An assessment of the South African agro-food sector - Monaheng, Koaile (Department of Environmental and Geographical Science, 2025)
Climate change is one of the most pressing issues affecting humanity today and Africa is one of the region's most vulnerable to climatic shocks such as extreme weather events and climate-driven disasters. Businesses are not immune to these shocks, as profit margins and assets are affected by hazards such as floods and wind on property damage, as well as heatwaves and droughts affecting agricultural yields, water availability and commodity prices. Under the fast-growing uptake of Environmental Social Governance (ESG), companies have had to evaluate their non-financial impact on society and the environment to not only improve their long-term business sustainability, but also to mitigate the associated risks. In South Africa, ESG-related regulations and laws encouraging responsible business practice forefront sustainability as a prerequisite for value-creation and legitimacy. Whilst there has been a climate corporate accountability analysis of carbon-intensive sectors such as mining and energy in South Africa, c